Global Actors’ Effort towards Gender Equality in Women's Health in East and Southern Africa - Putri, Alvela Salsabilah; Choirunissa, Puti Jasmine; Salma, Riana (UI Scholars Hub, 2021)
According to 2020 UNAIDS data, there are approximately 20,700,000 people infected with HIV, with 12,900,000 infected are women in Eastern & Southern Africa. This condition is caused by the lack of health rights for women which is also based on the limited rights of women to matters such as education, employment and finance. This study aims to examine the role of global government in accommodating global actors to address issues of gender equality in women's health in Eastern and Southern Africa. This research is built on the concept of global governance theory and feminism. The research method used is qualitative research methods using case studies. This paper concludes that global actors (governmental and non-governmental) make important contributions through international cooperation and produce various programmes for women's empowerment and health assistance. These programmes and assistance are producing slow but steady changes to gender equality and the well-being of women in the Eastern and Southern Africa region. Because through these various health programmes and assistance, women in the Eastern and Southern Africa region can optimise their rights as women as well as human beings.